Terahertz: dictating the frequency of life. Do macromolecular vibrational modes impose thermal limitations on terrestrial life?. Issue 136 (15th November 2017) - Hand, Kieran; Yates, Edwin
Abstract : Conditions on exoplanets include elevated temperatures and pressures. The response of carbon-based biological macromolecules to such conditions is then relevant to the viability of life. The capacity of proteins and ribozymes to catalyse reactions or bind receptors, and nucleic acids to convey information, depends on them sampling different conformational states. These are determined by macromolecular vibrational states, or phonon modes, accessible using terahertz (THz: 10 12 Hz) absorption spectroscopy. THz spectra of biological macromolecules exhibit broad absorption at approximately 6 THz (equating to approx. 280 K) corresponding to dense transitions between phonon modes. There are also troughs at approximately 10 THz (approx. 500 K) implying diminishing numbers of available conformational states at higher temperatures; hence, fewer routes by which biochemical processes can be realized, as equilibrium is approached. Could this conformational bottleneck hinder the operation of biological macromolecules at higher temperatures? We suggest that the troughs at approximately 10 THz in absorbance spectra indicate that the hydrogen bonds, charge interactions and geometry of biological macromolecules associated with terrestrial life impose fundamental vibrational properties that could limit the upper temperature at which they may function.